(3fbO GdCQGA GdefWbjI hMd eTcdGJgGs - (3GdfLaj, , GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3eMeO LhGO Hf YHO GdgGOj GdeXaQs)
(3ChdgG (B:s
(3ChdgG(B: (3bGdhG(B: (3Ef GdebOeI JbQC HcSQ GdOGd haJMgG, hjQO Ydjge (B.. (3ChdG(B: (3CfgG dG jUM cSQ GdOGd efgG dCfg HGdcSQ dG HO hCf Jchf GSe aGYd ef bOe (B((3HJTOjO GdOGd(B) (3hgj dG JNdh EeG ef GdeJYOj efgs
(3BNQgG (B:s
(3BNQgG(B: (3hLhGHg Cf djS ZQVge Pdc cdjI Hd ZQVge Cfg de jcf ajg JMUjd eLghd ef eYdhe ceG aj GdJYQja GdMbjbj aEf aj GdJYQja GdMbjbj cGf GdeLghd faS GdeYQa hHYO GdJYQja jYde Hg HNdGa GddaXj aEf faS GdeYQa eYdhe hdcf fLgd OdGdI GdaX Ydjgs
(3efbhdI Yf fSNI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs